SOLID OXIDE FUEL CELLS BASED ON A METAL CARRIER - Opakhai, С.; Kuterbekov, К.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In this short review article, all generations of solid oxide fuel cells are discussed in detail. Special attention was paid to solid oxide fuel cells on a supporting metal base. Structures with a metal base are of great interest due to the possibility of quick start, greater reliability, mechanical stability and resistance to thermal cycling. The advantages and disadvantages of metal supports based on Ni, FeNi, NiCrAlY and ferritic stainless steel were discussed in detail. The analysis of the work of leading scientists of the world on this topic research. Based on these analyzes, it is important to note that at present, solid oxide fuel cells based on a Ni-Al carrier is the most promising and economically efficient in the world.